Estimating a logistic Weibull mixture models with long-term survivors. - Abu Bakar, Mohd Rizam; Daud, Isa; Ibrahim, Noor Akma; Desi Rahmatina, (Universiti Teknologi Malaysia, 2006)
The mixture model postulates a mixed population with two types of individuals, the susceptible and long-term survivors. The susceptibles are at the risk of developing the event under consideration. However, the long-term survivors or immune individuals will never experience the event. This paper focuses on the covariates associated with individuals such as age, surgery and transplant related to the probability of being immune in a logistic Weibull model and to evaluate the effect of heart transplantation on subsequent survival.